2005
DOI: 10.1016/j.neuropsychologia.2004.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Co-activation of the amygdala, hippocampus and inferior frontal gyrus during autobiographical memory retrieval

Abstract: Functional MRI was used to investigate the role of medial temporal lobe and inferior frontal lobe regions in autobiographical recall. Prior to scanning, participants generated cue words for 50 autobiographical memories and rated their phenomenological properties using our autobiographical memory questionnaire (AMQ). During scanning, the cue words were presented and participants pressed a button when they retrieved the associated memory. The autobiographical retrieval task was interleaved in an event-related de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
150
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(179 citation statements)
references
References 99 publications
22
150
0
7
Order By: Relevance
“…In patients with frontotemporal lobar degeneration, episodic autobiographical memory as assessed by the Autobiographical Interview was related to left inferior parietal parenchymal volume (along with bilateral temporal and left posterior cingulate/retrosplenial volumes; McKinnon et al, in press). Consistent with these patient reports, several functional neuroimaging studies of autobiographical recollection have revealed significant lateral parietal activity (e.g., Addis et al, 2004;Gilboa et al, 2004;Greenberg et al, 2005;Levine et al, 2004; for a review, see Svoboda et al, 2006), in addition to medial parietal, retrosplenial, and posterior cingulate activity. For example, Levine et al (2004) played back audiotapes of descriptions of real-life experiences to volunteers who had recorded them over several weeks.…”
Section: Resultssupporting
confidence: 62%
“…In patients with frontotemporal lobar degeneration, episodic autobiographical memory as assessed by the Autobiographical Interview was related to left inferior parietal parenchymal volume (along with bilateral temporal and left posterior cingulate/retrosplenial volumes; McKinnon et al, in press). Consistent with these patient reports, several functional neuroimaging studies of autobiographical recollection have revealed significant lateral parietal activity (e.g., Addis et al, 2004;Gilboa et al, 2004;Greenberg et al, 2005;Levine et al, 2004; for a review, see Svoboda et al, 2006), in addition to medial parietal, retrosplenial, and posterior cingulate activity. For example, Levine et al (2004) played back audiotapes of descriptions of real-life experiences to volunteers who had recorded them over several weeks.…”
Section: Resultssupporting
confidence: 62%
“…y-axes represent average signal change. From "Co-Activation of the Amygdala, Hippocampus and Inferior Frontal Gyrus During Autobiographical Memory Retrieval," by D. L. Greenberg et al, 2005, Neuropsychologia, 43, p. 665. Copyright 2005 by Elsevier.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to address some of these issues, Greenberg et al (2005) used an event-related fMRI paradigm to examine emotional autobiographical memory. In this study, participants were presented with self-produced autobiographical memory cues derived from a prescanning session.…”
Section: Autobiographical Retrievalmentioning
confidence: 99%
“…While the first route is thought to be mostly mediated by the hippocampus and prefrontal cortex, the amygdala is thought to be engaged in the emotional reactions to memories, but these systems are highly interlinked (e.g., Greenberg et al 2005). Therefore, it is also of interest to know whether these routes can be affected separately.…”
mentioning
confidence: 99%